Aging, care and dependency in multimorbidity: how do relationships affect older Bangladeshi women's use of homecare and health services?. (2nd November 2022) - Hamiduzzaman, Mohammad; Torres, Stacy; Fletcher, Amber; Islam, M. Rezaul; Siddiquee, Noore Alam; Greenhill, Jennene
ABSTRACT: Gender issues can create major barriers to healthcare utilization for older women with multimorbidity, especially in developing countries like Bangladesh. Elderly rural women in Bangladesh, are the poorest of the poor, and the women with multimorbidity live in a regulated family atmosphere. This study explored the relationship dimensions of older women with multimorbidity in homecare and their utilization of health services. To gain a deeper understanding of these complex issues, a qualitative case study was conducted. Semi-structured, in-depth interviews were conducted with 11 health staff and 22 older women with multimorbidity, living in three residential communities of the Sylhet District, Bangladesh. Our analysis used critical thematic discourse, a technique developed from Axel Honneth's recognition-and-misrecognition theory. Seven relationship dimensions have been identified, and grouped under three major themes: intimate affairs [marital marginalization and parent-children-in law dynamics]; alienation in community relationships [patriarchal sibling relationships, neighborhood challenges, and gender inequality in interactions]; and legal disconnections [ignorance of rights and missed communication]. Our findings revealed a lack of understanding of the women's multimorbid care needs and patriarchal marginalization in family. This lack of understanding together with poor peer-supports in healthcare is perpetuated by misrecognition of needs from service providers, resulting in a lack of quality and poor utilization of homecare and health services. Understanding the high needs of multimorbidity and complexities of older women's relationships can assist in policy decisions. This study deepens our understanding of the ways gender inequality intersects with cultural devaluation to reduce the well-being of older women in developing countries.